Surgical anesthesia in a patient with a pheochromocytoma crisis supported by ECMO: a case report - Minjuan Chen; Wei Yan; ZhiHai Yang; Tao Hong; Lingling Jin; Donghang Cao; Yixiao GU (Journal of Cardiothoracic Surgery)
Abstract Pheochromocytoma is rare in clinical practice, with patients typically presenting with headache, high blood pressure and sweating. Patients who develop a pheochromocytoma crisis are particularly rare. This report describes the case of a patient in a pheochromocytoma crisis who presented with severe cardiogenic shock, acute respiratory failure, and acute coronary syndrome. The patient underwent surgery under general anesthesia with ECMO support and was discharged in good health.